GREENPEACE ADVOCACY AND INDIGENOUS FOREST GOVERNANCE PAPUA: THE AWYU-MOI CASE, 2021-2025 - Nurul Fadhilah Syam (Forestry Study Program University Of Mataram, 2026)
Papuan indigenous people depend on customary forests for their social, cultural and economic survival. But it’s under increasing threat from deforestation, plantation expansion and overlapping land-use permits. This study aims to analyze Greenpeace's strategy through the TAN framework in advocating for the protection of Papuan customary forests in the Awyu and Moi cases (2021–2025). This study uses descriptive qualitative methods based on the analysis of legal documents, campaign reports, and secondary data. This study explores how Greenpeace implements the TAN strategy through information, symbolic, influence, and accountability politics. Boomerang politics brings local issues into the international environmental and political agenda through global campaigns, media exposure, and transnational advocacy networks. The novelty of this study lies in combining the TAN framework and boomerang patterns to explain customary forest advocacy in Papua, particularly in the cases of Awyu and Moi, which are underrepresented in previous research. The results show that Greenpeace's advocacy increased public awareness, legal and political pressure for customary forest protection, and Indigenous Peoples' participation in environmental governance discussions. Although this study does not claim that advocacy directly reduced deforestation, it demonstrates Greenpeace's contribution to strengthening the monitoring of forest conversion policies and strengthening the discourse of sustainable forest management in Papua.